Current Options in the Treatment of COVID-19: A Review - Teimury A; Mahmoodi Khaledi E (Dove Medical Press, 2020)
Azadeh Teimury, Elahe Mahmoodi Khaledi Department of Cell and Molecular Biology, Faculty of Chemistry, University of Kashan, Kashan, IranCorrespondence: Elahe Mahmoodi KhalediDepartment of Cell and Molecular Biology, Faculty of Chemistry, University of Kashan, Kashan, IranTel +9831-55913042Fax +9831-55511121Email e.mahmoodi_kh@kashanu.ac.irAbstract: Novel Coronavirus, also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in December 2019 in China and spread rapidly all around the world infecting many people. To date, no specific vaccines and drugs have been developed for this disease. Also, due to the COVID-19 pandemic and high prevalence of the infected patients, the drugs and the therapies of other past viral epidemics have been used for this disease. Many studies have been performed on the specific treatments to find whether or not they are effective on COVID-19 patients. In this review, we collected information about the most widely used drugs to treat COVID-19 (coronavirus disease 2019) belonging to groups of antivirals, antibiotics, immune modulators, and anticoagulants. Some of these compounds and drugs were used directly by inpatients, so researchers have examined others in laboratory conditions. This study considered the pros and cons of using these treatments separately and together and compared their results. By studying this review, we hope to provide useful information for researchers.Keywords: SARS-CoV-2, COVID-19, antiviral drugs, antibiotics, immune modulators, anticoagulants